ASSOCIATION BETWEEN VITAMIN D DEFICIENCY, HYPERHOMOCYSTEINEMIA, AND LIPID PROFILE IN ACUTE CORONARY SYNDROME PATIENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute coronary syndrome (ACS) is a major cause of morbidity and mortality worldwide. Emerging evidence suggests that vitamin D deficiency, elevated serum homocysteine levels, and lipid abnormalities contribute significantly to the development and progression of coronary artery disease. This study was conducted to evaluate the association of serum vitamin D, serum homocysteine, and lipid profile in patients with ACS. Methodology: This hospital-based observational study was conducted in the Department of Emergency Medicine at from February 2025 to December 2026. A total of 96 patients diagnosed with ACS, including ST-segment elevation myocardial infarction (STEMI), non-ST-segment elevation myocardial infarction (NSTEMI), and unstable angina, were included in the study. Serum vitamin D, serum homocysteine, and lipid profile parameters were estimated using the Vitros 5600 automated analyzer. Statistical analysis was performed using SPSS version 25.0, and a p-value